2014
DOI: 10.4103/0976-3147.127865
|View full text |Cite
|
Sign up to set email alerts
|

Effect of type of secondary task on cued gait on people with idiopathic Parkinson′s disease

Abstract: Introduction:The purpose of this study was to find out the effect of the secondary cognitive and motor task on cued gait in people with Idiopathic Parkinson's disease (PD).Design and Setting:A repeated measure same subject design carried out at All India Institute of Medical Sciences, Neurology Department, New Delhi.Materials and Methods:The subjects were made to walk in random order on a paper walkway under three conditions: Free walking with cues at preferred walking speed, coin transference while walking wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
(40 reference statements)
1
5
0
Order By: Relevance
“…In addition, Chawla et al suggested that FOG also involved the perception-cognition system that is mediated mainly by the frontal cortex. PD patients may recruit attention and cognition resources to compensate for the impairment in motor function to achieve a more normal gait, revealing that cognition-related damage to the frontal cortex is correlated with FOG (Chawla et al, 2014). Taken together, our findings reinforced that frontal gyrus dysfunction, especially in the MFG, is a key cortical pathogenic hub in PD-FOG patients.…”
Section: Discussionsupporting
confidence: 68%
“…In addition, Chawla et al suggested that FOG also involved the perception-cognition system that is mediated mainly by the frontal cortex. PD patients may recruit attention and cognition resources to compensate for the impairment in motor function to achieve a more normal gait, revealing that cognition-related damage to the frontal cortex is correlated with FOG (Chawla et al, 2014). Taken together, our findings reinforced that frontal gyrus dysfunction, especially in the MFG, is a key cortical pathogenic hub in PD-FOG patients.…”
Section: Discussionsupporting
confidence: 68%
“…This approach proposes a unique assessment of CMI as well as allowing analysis of dual task interference from two cognitive tasks (cognitive-cognitive interference) or two motor tasks (motor-motor) performed simultaneously. Evidence suggests that the pairing of tasks is important in determining the effect of dual task interference, measured as task performance outcomes [ 7 9 ]; compare [ 10 ]. However, information processing creates a cognitive load regardless of the modality of task.…”
Section: Measuring Dual Task Performancementioning
confidence: 99%
“…Previous studies have indicated, however, that performing two tasks simultaneously may negatively impact gait performance 1 3 . Dual task interference impacting gait performance has been observed not only in healthy subjects 4 6 , but also in subjects with neurological disorders 4 , 7 10 . In stroke individuals, reductions in speed, cadence, and stride length, as well as increases in stride time during cognitive-motor dual tasking have been reported 4 , 8 10 .…”
Section: Introductionmentioning
confidence: 99%